ASUHAN KEBIDANAN PADA Ny. “A” MASA HAMIL, PERSALINAN, MASA NIFAS, NEONATUS, DAN KELUARGA BERENCANA DI UPT PUSKESMAS SOOKO MOJOKERTO - Sulis Diana, M.Kes; Nanda Putri Intan Lesari (MEDICA MAJAPAHIT, 2021)
The Maternal Mortality Rate in Indonesia is still high. The maternal mortality rate in Indonesia stands at 305 per 100,000 live births while the infant mortality rate is at 23 per 1000 live births. The existence of comprehensive monitoring through Continuity of care (COC) is expected to reduce maternal And infant mortality as small as possible. Comprehensive services, which were complete services, starting from the period of pregnancy, parturition, post partum, neonatal, and family planning, were carried out with midwifery management and SOAP documentation. Midwifery care was given to Mrs “A”G1P000. 38 weeks of gestational age were done at the Puskesmas Sooko working area on February 25-May 16 2019. The results of midwifery care performed on Mrs "A"pregnancy were obtained physiological complaint. During parturition Mrs. "A" was referred to Hassanah Hospitaland had caesarea section due to elongeted duration of second stage, during the puerperal period Mrs. "A"went physiologically. Baby Mrs "A" was born normal with a body weight of 3,900 grams and a body length of 52 cm, male sex. Neonatal period ran physiologically. The contraceptive method used by Mrs. "A" was 3 monthly contraceptive injection. Based on midwifery care at Mrs. "A" it is very important to stay relaxed and prepare theirself when facing parturition so as not to worry so that there is no increase in blood pressure. Midwives must provide comprehensive care so that mothers receive optimal care, the health status of pregnant women until parturition through services for pregnant women to postpartum will increase